Presidential Candidate Figures Towards the Vision of Advanced Indonesia 2045 - Pambudi, Rakhmat Dwi (Forum Ilmu Sosial, 2023)
Achieving the Vision of Advanced Indonesia 2045 can only be achieved through a quality leadership and development planning process. Therefore, the presidential election in 2024 as part of the development planning process is important to make development implementation successful. This research is quantitative descriptive. Data collection techniques in this research took the form of online surveys and interviews. The respondents in this research were students of the Islamic Economics Study Program, Faculty of Islamic Economics and Business, UIN Walisongo Semarang who had taken the Development Planning Course. The research results show that respondents consider the economic and industrial sectors, as well as human resource development, especially the education sector, to be the main fokus in the RPJMN for the 2025-2029 period. Thus, a state leader is needed who has an honest and trustworthy character, as well as being intelligent and innovative in carrying out national development priorities. The majority of respondents view track record as one of the considerations in choosing a presidential candidate. Respondents obtained most of the information regarding presidential candidates from the internet.